(untitled) (mathematica didactica, 2013)
During the last few years in Germany there have been conducted numerous studies concerning mathematical giftedness especially in primary school age. Research projects in the field of mathematics didactics include for instance studies on models of giftedness, possibilities of identification and fostering of gifted students, their problem solving processes and competencies, studies on special characteristics of mathematical giftedness, or on gender-specific aspects in this area. I want to describe some important didactic research projects and interrelations between them. Thereby I will also introduce the other contributions in this issue.